The effect of environmental factors on the productivity of the saffron plant, Crocus sativus. L in Rif Damascus Governorate – Syria. (Damascus University Journal of agriculture sciences, 2026)
The research was carried out at the General Authority for Scientific Agricultural Research, Damascus Rural Research Center (Sarghaya and Taybeh Research Stations), Syria, during the 2019 and 2020 agricultural seasons, with the aim of studying the effect of environmental factors of the sites where saffron plants (Crocus sativus. L.) are grown on productivity indicators (seeds and corms). for plants.The results of the experiment showed that the prevailing climatic conditions in the Sarghaya region increased floral growth indicators (average number of flowers and their wet weight, average length of stigmas and their dry weight) and the number of corms of saffron plants grown there compared to their counterparts grown in the conditions of the Taybeh region, with statistical significance. The 2020 season was significantly superior to the 2019 season in terms of the average number of flowers and the average wet weight of the flowers (0.63 flowers, 0.19 g), while the latter was superior to the 2020 season, with statistical significance, in the average length of the flower stigmas and the dry weight of the stigmas (3.592 cm, 0.035 g). Regarding the weight of the corms, there was a significant effect in both sites, and the highest weight was reached in the Al-Tayba site with an average weight of (14.95) grams. The effect was significant on the average yield in both sites, and the highest productivity was reached in the Al-Tayba site with an average corm weight of (0.26) kg/dunum. The same significant effect was also observed. In terms of the average yield produced in the second season (0.28 kg/dunum) than that produced in the first season (0.21 kg/dunum), the Sarghaya site was superior in the average number of corms, reaching (19.20) corms, and the second season outperformed the first season, reaching (23) corms. Compared to the first season (4.6) as a result.As for the content of the stigmas of active substances, no significant differences were observed between the two cultivation sites (Taybeh and Serghaya) in the average content of the stigmas of crocin (158.73, 182.85 (g/gµ)), respectively, or in the average content of the stigmas of safrnal (23.50 and 23.90 (g). /gµ), respectively. As for the average content of stigmas of picrocrocin, the Sarghaya site was 74.80 (g/gµ) superior to the Taiba site, 56.06 (g/gµ), respectively.
Keywords: saffron; environmental factors; Taybeh site; Sarghaya site; floral indicators; corm indicators